Decolonising Data in the Age of Data Colonialism: An Interview with Professor Nick Couldry - Maria Pia Ester CRISTALDI (Etkileşim)
In May 2024, the Faculty of Communication at Üsküdar University hosted the 11th International Communication Symposium, which this year has been delineated on the overarching theme ‘Digital Inequality and Data Colonialism’. Among the scholars and subject matter experts serving as keynote speakers during its proceedings, Prof. Dr. Nick Couldry along with Prof. Dr. Ulises A. Mejias- gave an insightful keynote speech entitled “Data Grab: The New Colonialism of Big Tech”, which focused on the subjects explored in the groundbreaking research recently published by the two scholars and entitled Data Grab: The New Colonialism of Big Tech and How to Fight Back. In this context, as founders of the concept of data colonialism, Couldry and Mejias discussed further implications of this concept and how Big Tech companies are nowadays grabbing users’ data, exploiting labour and connections for their profit